(untitled) - Rostasova, Maria; Batka, Miroslav (Doprava a spoje, 2005)
The contribution obtains the specific analyze of method SWEX - as a measurement of general postal service levels in Sweden Post. This postal organization decided to complement the E2E measurements of single piece priority mail with an AMQM - Automatic Mail Quality Measurement monitoring, because the customer's most important requirement is that Posten deliver its services on time